Bridging the Gap: Assessing Nurses' Safe Handling and Administration of Chemotherapeutic Drugs in a Tertiary Health Facility, Benin City, Nigeria - Josiah, Uzezi; Ehwarieme, Timothy A.; Uzezi, Hope (Fundamental and Management Nursing Journal, 2025)
Introduction: The administration of chemotherapeutic drugs requires specialized knowledge and skills to ensure optimal patient outcomes and minimize risks. While global guidelines emphasize the importance of safe chemotherapy administration, there is a lack of context-specific data on the knowledge and practices of nurses in tertiary health facilities in Benin City. This study addresses the gap by providing empirical evidence on their competencies and challenges. Hence this study aimed to assess the knowledge and practices of safe handling and administration of chemotherapeutic drugs amongst tertiary health facility, Benin City. Methods: The study adopted a descriptive cross-sectional study design among randomly selected 278 nurse working in the selected hospital. A researcher developed structured validated questionnaire was used as instrument of data collection. Data collected was analyse using descriptive statistics while hypothesis tested using multiple logistic regression at 5% level of significant. Data analysis was done using the IBM Statistical Package for Social Sciences (SPSS) version 28.0 for windows. Results: Overall 17% of participants had poor knowledge, and 63% had fair knowledge. More than half (51%) exhibited poor practice. Most significant factors supporting the safe handling and administration of chemotherapeutic drugs are Training and Certification (3.94), Incident Encounters (3.73), Protocol Adherence (2.93), and Utilization of PPE (2.82). Being married: (OR = 1.136 (95% C.I: 1.10–3.83, p = 0.7369),   Female (OR = 4.90, 95% CI: 0.23–3.54, p = 0.479), 18–34 years (OR = 7.03, 95% CI: 0.06–8.28, p = 0.298) , Bachelor Degree (OR = 7.69, 95% CI: 0.05–7.10, p = 0.174) have higher odds of exhibiting a higher level of practice compared to other categories but not statistically significant. Conclusions: The study found that nurses have moderate knowledge and practice levels in handling chemotherapeutic drugs but still face significant gaps. It highlights the need for targeted interventions, in-service education, and institutional policies to improve competency and ensure safe chemotherapy administration.